1993
DOI: 10.1111/j.1559-1816.1993.tb01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximal and Distal Predictors of Homophobia: Framing the Multivariate Roots of Outgroup Rejection1

Abstract: A proximal‐distal theoretical framework was developed to examine the multivariate roots of homophobia. Using data from a sample of 288 undergraduates who had participated in a computer‐assisted panel study over a three‐year period, the effects on homophobia of distal and proximal family factors (e. g., parental education and family environment), distal and proximal individual factors (e. g., personality constructs and current beliefs), and proximal individual‐situational factors (e. g., acquaintance with homos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 35 publications
2
33
1
1
Order By: Relevance
“…In a mixed-gender college students sample, physical self-esteem (but not general self-esteem) was positively associated with homophobic attitudes [26]. Another study found that general self-esteem was not correlated with attitude toward homosexuality among men or women, but gender-related selfesteem positively predicted homophobic attitudes among men [27].…”
Section: Self-esteem and Attitudes About Homosexualitymentioning
confidence: 94%
“…In a mixed-gender college students sample, physical self-esteem (but not general self-esteem) was positively associated with homophobic attitudes [26]. Another study found that general self-esteem was not correlated with attitude toward homosexuality among men or women, but gender-related selfesteem positively predicted homophobic attitudes among men [27].…”
Section: Self-esteem and Attitudes About Homosexualitymentioning
confidence: 94%
“…For instance, a consistent finding has been a significant positive relation between homophobia and authoritarianism (low tolerance of ambiguity, high cognitive rigidity, and adherence to authority over individual freedom; Herek, 1984;MacDonald & Games, 1974;Smith, 1971;Wylies & Forest, 1992). Homophobia has also been associated with traditional gender role attitudes (i.e., maintaining a clear and traditional distinction between the sexes, and between what is thought to be "male" and "female;" Aguero et al, 1984;Hudson & Ricketts, 1980;Smith, 1971), and with religious conservatism (Agnew, Thompson, Smith, Gramzow, & Currey, 1993;Forstein, 1988;Fyfe, 1983).…”
Section: Introductionmentioning
confidence: 90%
“…Analogous to the literature on racism, no research to date has explored the interrelationship of homophobia and rape myth acceptance. Homophobia, however, has also been found to be associated with sexism (Agnew, Thompson, Smith, Gramzow, & Currey, 1993;Campbell, Schellenberg, & Senn, 1997;Polimeni et al, 2000;Thompson, Gristani, & Pleck, 1985). Given the known relationship between sexism and rape myth acceptance, an investigation focused on the association between homophobia and rape myth seems warranted.…”
mentioning
confidence: 89%